2020
DOI: 10.1111/1744-7941.12270
|View full text |Cite
|
Sign up to set email alerts
|

To engage or not? Antecedents of employee engagement in Sri Lanka

Abstract: This study integrates the resource demand and social exchange perspectives and assesses if employer brand, organizational politics, self-efficacy, and family-work conflict predict employee engagement. Furthermore, this paper examines the impact of boundary conditions of employee engagement by focusing on exchange ideology and gender. Data were collected using questionnaires from 411 managerial employees working in licensed commercial banks in Sri Lanka. The results revealed that employer brand, perceived organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
3
11
0
Order By: Relevance
“…The results demonstrated that perceived organisational politics negatively influences engagement as expected. This finding is consistent with previous studies in politics and engagement relationship (Byrne et al , 2017; Karatepe, 2013; Mayuran and Kailasapathy, 2020). While challenging demands foster the work engagement, hindrance demands obstruct it (Crawford et al , 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results demonstrated that perceived organisational politics negatively influences engagement as expected. This finding is consistent with previous studies in politics and engagement relationship (Byrne et al , 2017; Karatepe, 2013; Mayuran and Kailasapathy, 2020). While challenging demands foster the work engagement, hindrance demands obstruct it (Crawford et al , 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Along with previous studies (Crawford et al , 2010; Mayuran and Kailasapathy 2020), the current study is showing that organisational politics, as a hindrance demand, reduces engagement. Therefore, this study also suggests that organisational politics could be considered as an organisational-level demand in the JD-R model (Landells and Albrecht, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…According to Baker et al, burnout develops in a scenario where there is an imbalance between demands and resources at work [ 34 ]. On the other hand, work engagement is decreased by burnout [ 45 , 46 , 47 , 48 ] and increased by resources [ 42 , 43 , 44 ]. Our results are consistent with the extensive literature in the field and support the application of the JD-R model in the foodservice context.…”
Section: Discussionmentioning
confidence: 99%
“…A resource decline affects both burnout and work engagement [ 41 ]. Over time, studies have confirmed the importance of resources in increasing work engagement [ 42 , 43 , 44 ]. Thus, work engagement is reduced when the worker has access to fewer and fewer resources.…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…Hence, this finding emphasizes the need for examining the antecedents of employee engagement in the Sri Lankan context. In the study conducted by Mayuran and Kailasapathy (2020) among the managerial level employees from licensed commercial banks in Sri Lanka, the antecedents of employee engagement were examined. The study revealed that employer brand, perceived organizational politics, and self-efficacy were significantly related to employee engagement.…”
Section: Introductionmentioning
confidence: 99%